2018
DOI: 10.1038/s41434-018-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

AAV1.NT-3 gene therapy increases muscle fiber diameter through activation of mTOR pathway and metabolic remodeling in a CMT mouse model

Abstract: Neurotrophin 3 (NT-3) has well-recognized effects on peripheral nerve and Schwann cells, promoting axonal regeneration and associated myelination. In this study, we assessed the effects of AAV.NT-3 gene therapy on the oxidative state of the neurogenic muscle from the TremblerJ (Tr ) mice at 16 weeks post-gene injection and found that the muscle fiber size increase was associated with a change in the oxidative state of muscle fibers towards normalization of the fiber type ratio seen in the wild type. NT-3-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…As all these pharmacological treatments require a regular and permanent treatment with potential side effects on the long term, gene therapy represents an attractive alternative. Indeed, an indirect gene therapy approach consists of the transduction of muscle cells to increase their production of neurotrophin 3 in order to promote axon survival is in clinical trial phase I/IIa (NCT03520751) [50,65]. Here we investigated the conditions for a successful gene therapy approach directly targeting mSC, the defective cells in the disease, through an intra nerve delivery.…”
Section: Discussionmentioning
confidence: 99%
“…As all these pharmacological treatments require a regular and permanent treatment with potential side effects on the long term, gene therapy represents an attractive alternative. Indeed, an indirect gene therapy approach consists of the transduction of muscle cells to increase their production of neurotrophin 3 in order to promote axon survival is in clinical trial phase I/IIa (NCT03520751) [50,65]. Here we investigated the conditions for a successful gene therapy approach directly targeting mSC, the defective cells in the disease, through an intra nerve delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, since the relevance of BDNF, NGF and NT-3 on different aspects of satellite cell function and muscle regeneration has been well documented [30][31][32]40,56], we suggest that higher expression of several neurotrophins and the p75 NTR receptor observed in EOM-derived progenitors, could be endowing these cells with their highly regenerative properties and thus could be protecting these craniofacial muscles against certain inflammatory and wasting diseases.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, only a few studies have focused their attention on NT-3 role in skeletal muscle physiology [38,39]. Recently, Yalvac et al [40] demonstrated that NT-3, acting through direct activation of the mTOR-TrkC related pathway, increases muscle fiber diameter in the neurogenic muscle from the Trembler-J mice.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts concur to the repair process by depositing extracellular matrix, but excess extracellular matrix deposition interferes with the regeneration process. 47 Also, there is evidence that neurotrophin 3 directly influences the protein synthesis and metabolic remodelling in neurogenic muscle via activation of a TrkC/Akt/mTORC1 pathway in myofibers but not myoblasts, 48 and that nitrogen permease regulator like-2, a proposed tumour suppressor gene, activates mTORC1 causing muscle hypertrophy with increased numbers of fast-twitch, Type II glycolytic muscle fibres 49 ( Figure 2). DAMP, damage-associated molecular pattern; FAPs, fibro/ adipogenic precursors; IL-4, interleukin-4; SC, satellite cell.…”
Section: Altered Myofiber Metabolismmentioning
confidence: 99%
“…Supporting this possibility is the observation that the Nrf2 activator, sulforaphane, enhances running capacity in rats by up-regulation of Nrf2 signalling and downstream genes and attenuates muscle fatigue via reduction of oxidative stress caused by exhaustive exercise. 47 Also, there is evidence that neurotrophin 3 directly influences the protein synthesis and metabolic remodelling in neurogenic muscle via activation of a TrkC/Akt/mTORC1 pathway in myofibers but not myoblasts, 48 and that nitrogen permease regulator like-2, a proposed tumour suppressor gene, activates mTORC1 causing muscle hypertrophy with increased numbers of fast-twitch, Type II glycolytic muscle fibres 49 ( Figure 2). However, constitutive activation of mTORC1 can affect global metabolic changes and elicit late-onset myopathies.…”
Section: Figurementioning
confidence: 99%